CHARACTER AND MORAL VALUE IN “THE SOUND OF MUSIC” BY ROBERT WISE - AAN HANDAYANI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This research aims to analyze the characters and moral values ??contained in the film